James Petigru Boyce papers - Boyce, James Petigru, 1827-1888.
Accounts as executor of the estate of Ker Boyce, acts of South Carolina legislature, genealogical notes, and clippings. Corresondents include John Albert Broadus and Christopher G. Memminger
Clergyman, educator, and founder and president (1858-1888) of the Southern Baptist Theological Seminary.
Collection material in English.
Keywords: Boyce, Ker; Broadus, John Albert, -- 1829-1895 -- Correspondence; Memminger, C. G. -- 1803-1888 -- Correspondence; Boyce family; South Carolina. -- General Assembly; Clergy; Educators; Theological seminary presidents